The CDS market reaction to loan renegotiation announcements - Silaghi, Florina; Martín-Oliver, Alfredo; Sewaid, Ahmed (Journal of Banking & Finance, 2022)
This paper investigates the impact of loan renegotiations on firms’ credit risk using the CDS market as a measure of credit risk. Using a sample of public US firms for 2010–2017, we document a significant decrease in CDS spreads and returns that we interpret as evidence of a certification effect. The finding suggests that the loan renegotiations are on average beneficial for the firm. The strongest reactions are for material amendments such as line of credit amount or tranche amount. Additionally, we find negative stock market returns, although barely statistically significant. Moreover, we identify an anticipation effect of up to 30 days before the announcement date on the CDS market, possibly due to informed trading by CDS banks of their speculative-rated borrowers’ CDS contracts. Finally, we show that firm-specific CDS returns lead idiosyncratic stock returns, especially around the announcement date and for speculative-rated firms.